2017
DOI: 10.1111/anec.12511
|View full text |Cite
|
Sign up to set email alerts
|

The effect of head‐up tilt upon markers of heart rate variability in patients with atrial fibrillation

Abstract: In the SR cohort, increasing age was associated with fewer HRV changes on tilting. Patients with AF had blunted HRV responses to tilting, mirroring those seen in an age matched SR group. It is feasible to measure HRV in patients with AF and the changes observed on HUT are comparable to those seen in patients in sinus rhythm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
1
6
1
Order By: Relevance
“…Access to data from patients with AF during other tilt-inclinations could potentially be used to refine the model to take the degree on inclination into account. The tilt-induced changes in RR series irregularity observed in the present study are in line with the results in Patel et al (2018) , where a decrease in RR sample entropy in response to HUT in patients with AF was reported. The tilt-induced changes in RR series irregularity observed in the present study are also in line with the changes reported for patients in normal sinus rhythm during HUT ( Porta et al, 2007 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Access to data from patients with AF during other tilt-inclinations could potentially be used to refine the model to take the degree on inclination into account. The tilt-induced changes in RR series irregularity observed in the present study are in line with the results in Patel et al (2018) , where a decrease in RR sample entropy in response to HUT in patients with AF was reported. The tilt-induced changes in RR series irregularity observed in the present study are also in line with the changes reported for patients in normal sinus rhythm during HUT ( Porta et al, 2007 ).…”
Section: Discussionsupporting
confidence: 93%
“…While ANS modulation has been extensively studied during normal sinus rhythm ( Porta et al, 2007 ; Porta et al, 2015 ; Sassi et al, 2015 ; Patel et al, 2018 ), no attempts have been made towards the estimation of ANS modulation during persistent AF. The present study is a first step towards developing a model of the AV node that will ultimately be used to quantify ANS modulation on a patient specific basis by fitting to RR interval series and information on atrial electrical activity obtained from clinical ECG recordings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the effect the regularity of the RR series has in modelling AFR was further evaluated in the ¢ ME model showing a significant effect (b ¢ 3 = 0.105, p < 0.05). Previous studies have shown that the RR irregularity during AF change in response to changes in autonomic tone induced by drugs , Cygankiewicz et al 2015 and tilt-test (Patel et al 2018). However, it should be noted that increased RR irregularity may also be a direct effect of changes in atrial electrical activity as quantified by an increased AFR or variations in the atrioventricular node conduction (Plappert et al 2021).…”
Section: Discussionmentioning
confidence: 98%
“…[ 17 18 ] An increase in LF was seen in their studies which were a result mechanism reverse of above. [ 19 ]…”
Section: Discussionmentioning
confidence: 99%